Secret seven on the trail - Blyton, Enid (Hodder Children's London, 2002)
An enduringly popular series, now with fun new covers! Is something mysterious happening at Tigger's Barn? Peter thinks it's a hoax. Then Jack overhears an extraordinary conversation which lead the Seven on a trail of adventure!